Genome-wide identification and expression analysis of WRKY gene family members in red clover (Trifolium pratense L.) - Yuan, Guoxin; Zhang, Nijing; Zou, Yiming; Hao, Yaqi; Pan, Jiahao; Liu, Yongzhao; Zhang, Weiguo; Li, Beibei (Frontiers in Plant Science, 2023)
Trifolium pratense is an important legume forage grass and a key component of sustainable livestock development. Serving as an essential component, the WRKY gene family, a crucial group of regulatory transcription factors in plants, holds significant importance in their response to abiotic stresses. However, there has been no systematic analysis conducted on the WRKY gene family in Trifolium pratense. This study conducted a comprehensive genomic characterization of the WRKY gene family in Trifolium pratense, utilizing the latest genomic data, resulting in the identification of 59 TpWRKY genes. Based on their structural features, phylogenetic characteristics, and conserved motif composition, the WRKY proteins were classified into three groups, with group II further subdivided into five subgroups (II-a, II-b, II-c, II-d, and II-e). The majority of the TpWRKYs in a group share a similar structure and motif composition. Intra-group syntenic analysis revealed eight pairs of duplicate segments. The expression patterns of 59 TpWRKY genes in roots, stems, leaves, and flowers were examined by analyzing RNA-seq data. The expression of 12 TpWRKY genes under drought, low-temperature (4°C), methyl jasmonate (MeJA) and abscisic acid (ABA) stresses was analyzed by RT-qPCR. The findings indicated that TpWRKY46 was highly induced by drought stress, and TpWRKY26 and TpWRKY41 were significantly induced by low temperature stress. In addition, TpWRKY29 and TpWRKY36 were greatly induced by MeJA stress treatment, and TpWRKY17 was significantly upregulated by ABA stress treatment. In this research, we identified and comprehensively analyzed the structural features of the WRKY gene family in T.pratense, along with determined the possible roles of WRKY candidate genes in abiotic stress. These discoveries deepen our understandings of how WRKY transcription factors contribute to species evolution and functional divergence, laying a solid molecular foundation for future exploration and study of stress resistance mechanisms in T.pratense.